2015
DOI: 10.1007/s00198-015-3289-5
|View full text |Cite
|
Sign up to set email alerts
|

Marrow adipogenesis and bone loss that parallels estrogen deficiency is slowed by low-intensity mechanical signals

Abstract: LIV can mitigate adipocyte accumulation in OVX marrow and protect it by favoring osteoblastogenesis over adipogenesis. These data also emphasize the rapidity of bone loss with OVX and provide perspective in the timing of treatments for postmenopausal osteoporosis where sooner is better than later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…36,37 It is important to highlight that recent research has reported that repeated exposure to lowintensity vibration induced marked degeneration of murine knee joints, including meniscal tears and focal damage to the cartilage surface within the medial joint compartment. 38 From previous studies in our laboratory, 27,[39][40][41] we have not observed damage to connective tissues, whether bone, cartilage, tendon, IVD, muscle or ligament. Further, in clinical trials evaluating the capacity of LIV to preserve bone under conditions of disease or age, [42][43][44][45][46][47] no adverse event was reported relative to knee, hip or back pain.…”
Section: Low-intensity Vibration Increases Cartilage Thicknessmentioning
confidence: 54%
“…36,37 It is important to highlight that recent research has reported that repeated exposure to lowintensity vibration induced marked degeneration of murine knee joints, including meniscal tears and focal damage to the cartilage surface within the medial joint compartment. 38 From previous studies in our laboratory, 27,[39][40][41] we have not observed damage to connective tissues, whether bone, cartilage, tendon, IVD, muscle or ligament. Further, in clinical trials evaluating the capacity of LIV to preserve bone under conditions of disease or age, [42][43][44][45][46][47] no adverse event was reported relative to knee, hip or back pain.…”
Section: Low-intensity Vibration Increases Cartilage Thicknessmentioning
confidence: 54%
“…However, excessive BMAT accumulation is also observed following diverse clinical conditions such as exposure to radiation, chemotherapy, and glucocorticoid treatment, or following starvation, as in patients with anorexia nervosa . Furthermore, lifestyle influences (such as unloading of bones, seen in astronauts or during extensive bedrest) and obesity can also increase BMAT, whereas exercise and mechanical stimulation can decrease BMAT . Exercise may reduce BMAT by enhancing energy expenditure and FA β‐oxidation …”
Section: Bone Marrow Adipose Tissuementioning
confidence: 99%
“…These studies showed that LIV (0.2–0.3 × g , 90Hz, 15–30 min/day) was able to partially protect against estrogen-deficient bone loss and reduce the presence of adipocytes or adipogenic gene expression in bone marrow and muscle tissues. 70,174 …”
Section: Combating Obesity With Mechanical Signalsmentioning
confidence: 99%
“…63 MSC differentiation is also regulated by the Wnt signaling pathway, [64][65][66] and it is understood that osteoblastogenesis and adipogenesis in the marrow generally maintain an inverse relationship. Adipocyte commitment is often associated with reduced bone formation, as seen in models of microgravity, 67,68 ovarian hormone depletion, 69,70 and aging. 71 Through Wnt signaling or other osteogenic signaling pathways, it is plausible that MSC commitment to adipogenesis in the obese state can be controlled.…”
Section: The Bone Marrow Is a Dynamic Heterogeneous Environment And Hmentioning
confidence: 99%